Faecal parasites increase with age but not reproductive effort in wild female chimpanzees - Phillips, Sarah Renee (Philos Trans R Soc Lond B Biol Sci, 2020)
Energy investment in reproduction is predicted to trade off against other necessary physiological functions like immunity, but it is unclear to what extent this impacts fitness in long-lived species. Among mammals, female primates, and especially apes, exhibit extensive periods of investment in each offspring. During this time, energy diverted to gestation and lactation is hypothesized to incur short and long-term deficits in maternal immunity and lead to accelerated ageing. We examined the relationship between reproduction and immunity, as measured by faecal parasite counts, in wild female chimpanzees (Pan troglodytes schweinfurthii) of Kibale National Park, Uganda. While we observed higher parasite shedding (counts of eggs, cysts and larvae) in pregnant chimpanzees relative to cycling females, parasites rapidly decreased during early lactation, the most energetically taxing phase of the reproductive cycle. Additionally, while our results indicate that parasite shedding increases with age, females with higher fertility for their age had lower faecal parasite counts. Such findings support the hypothesis that the relatively conservative rate of female reproduction in chimpanzees may be protective against the negative effects of reproductive effort on health. This article is part of the theme issue ‘Evolution of the primate ageing process’.